Positioning performance of GNSS-PPP and PPP-AR methods for determining the vertical displacements - Akpinar, Burak (TAYLOR & FRANCIS LTD, 2023)
This study investigates the accuracy of vertical displacements monitored by Global Navigation Satellite Systems (GNSS) precise point positioning (PPP) with float-ambiguity solution and with ambiguity resolution (PPP-AR). For this purpose, a simulation was designed. The static GNSS observations were collected at a test point during different observation times over seven periods involving vertical displacements produced with a precision of less than one mm. Each set of GNSS observations was processed with both GNSS-PPP and PPP-AR methods. The results revealed that RMS values of PPP-AR solutions are about twice better than RMS values of PPP solution for all observation times and all vertical displacement values.
Keywords: GNNS; PPP; PPP-AR; Vertical displacements; GPS; DEFORMATION; RESOLUTION; ACCURACY; SERVICES; STATION; Engineering; Geology; Remote Sensing